Perbandingan Sensitivitas Metode SAW, MAUT dan WSM pada Anugerah Mutu Non-Akademik Universitas - Wonoseto, Muhammad Galih; Hunaif, Muhammad Abu Shaker (JISKA (Jurnal Informatika Sunan Kalijaga), 2025)
A Decision Support System works best with a suitable method. Unfortunately, not all methods are equally used. Two rarely used methods are the MAUT and WSM methods. To determine whether a method is more suitable for a case than another, a sensitivity test is conducted. By conducting sensitivity tests between the two methods and other commonly used methods, such as SAW, in the same case, it’s possible to compare the sensitivity percentages of the three. One case that can be helped by a Decision Support System using the three methods is the ANOMIK assessment at universities. The three methods produced the same best alternative, namely Faculty 9. After conducting a sensitivity test, the results showed that the WSM method was the most sensitive, with a value of 4.954%, followed by the SAW method with a value of 4.901%, and finally the MAUT method with a value of 3.844%.